(untitled) (Medical Forum Monthly, 2024)
Background: Ventricular Septal Defect (VSD) is commonest of all the congenital heart diseases. This is found as an isolated lesion as well as in association with other congenital cardiac lesions. The management and outcome of isolated VSD is not only dependent upon the size but also depends on the associated complications of ventricular septal defect (VSD). Pulmonary hypertension is not only the most common complication but also the most important indication of surgery in our setup. Objectives: To study the pattern of various types of ventricular septal defects (VSDs) and assessment of severity of associated pulmonary hypertension in our population. Study Design: Cross sectional descriptive study. Patients and Methods: The study was conducted at the paediatric cardiology department of The Children Hospital & The Institute of Child Health Multan, from October 2009 to March 2011. All patients with ages between 1 day to 15 years presenting with isolated VSD during the study period were studied using 2-D, continuous wave Doppler and color Doppler transthoracic echocardiography. Results: Out of 403 patients with isolated VSD, 288 were of perimembranous type (71.4%), 57 were of muscular type (14.2%), 19 were of doubly committed sub arterial (DCSA) type (4.7%) and 39 patients were having inlet VSD (9.7%). The mean age was 2.4 years. Females were 137 (34.0%) and males were 266 (66.0%). Pulmonary hypertension was present in 210 patients (52.1%). Amongst these mild pulmonary hypertension was present in 86 (40.9%), moderate in 65 (30.9%) and severe pulmonary hypertension was present in 59 (28.1%). Conclusion: Perimembranous (PM) VSD is the commonest type of ventricular septal defect presenting to our hospital. The incidence of pulmonary hypertension is very high (52.1%) and even severe pulmonary hypertension was found in about a quarter of the patients. This shows the degree of delay in surgery and the major reason is non availability of pediatric cardiac surgery centers in government setups.